Self-reported physician attitudes and behaviours towards incarcerated patients - Pierre, Kevin (Journal of medical ethics, 2022)
Physicians anecdotally report inquiring about incarcerated patients’ crimes and their length of sentence, which has potential implications for the quality of care these patients receive. However, there is minimal research on how a physician’s awareness of their patient’s crimes/length of sentence impacts physician behaviours and attitudes. We performed regression modelling on a 27-question survey to analyse physician attitudes and behaviours towards incarcerated patients. We found that, although most physicians did not usually try to learn of their patients’ crimes, they often became aware of them. We observed associations between awareness of a patient’s crime and poor physician disposition towards their patients and between physicians’ poor dispositions and lower reported quality of care. These associations suggest that awareness of a patient’s crime may reduce quality of care by negatively impacting physicians’ dispositions towards their patients. Future quantitative and qualitative studies, for example, involving physician interviews and direct patient outcome assessments, are needed to confirm these findings and further uncover and address hurdles incarcerated patients face in seeking medical care.